Potential benefits of blood flow restriction training in patients with type 2 diabetes: A narrative literature review - Trybulski Robert; Clemente Filipe Manuel; Biolik Grzegorz; Wilk Michał; Kużdżał Adrian (Biomedical Human Kinetics)
Study aim: This narrative review aims to critically discuss the potential beneficial effects of blood flow restriction (BFR) training on physiological outcomes, including muscle metabolism, insulin sensitivity, glucose metabolism, body composition, and cardiovascular health in type 2 diabetic individuals.